National advisory panels for childhood cancer in the United Kingdom: An evaluation of current practice and a best practice statement for the future. Issue 3 (24th December 2022) - Brown, Sarah; Chowdhury, Tanzina; Collin, Matthew; Grundy, Richard G.; Howell, Lisa; Ramanujachar, Ramya; Rees, Helen; Vora, Ajay; Gray, Juliet C.; Bate, Jessica
Abstract: Background: National advisory panels (NAPs) have been established for the care of children and young people (CYP) with cancer in the United Kingdom since 2011, with an increase in panel number in recent years. Their practice has not previously been reviewed; therefore, we sought to evaluate the role, practice and impact of six selected NAPs offering expertise in ependymoma, histiocytosis, leukaemia, neuroblastoma, renal tumours and sarcoma. Procedure: This service evaluation used mixed methodology, including review of NAP documentation, semi‐structured interviews with the NAP chairs and an analysis of the cases referred for discussion. Results: Total 1110 referrals were analysed. Results demonstrated the significant scope and amount of work undertaken by the NAPs, largely testament to the commitment of the panel members. Specific roles fulfilled have been highlighted, and NAP recommendations have been shown to influence clinical decision‐making and be implemented in the majority of cases. Despite widespread good practice, areas to address have been identified; these include clarity regarding NAP membership, consistency in recommendations, the consideration of holistic information to promote personalised management and the exploration of wider multidisciplinary team roles. Conclusions: In the context of increasing demand and the escalating number of NAPs, it is timely to consider how service improvement can be facilitated. Best practice guidelines have been formulated as a product of this study, to promote a sustainable and effective model for NAPs. Review and benchmarking national panel performance against these guidelines will drive high standards of care going forward and they should be embedded as standard practice.